Lessons from over 70 years of regional alignment processes in Europe for international higher education - Hans de Wit; Lizhou Wang (Emerald Publishing, 2024)
Purpose - This article provides an overview and analysis of 50 years of European policies, actions, and challenges to align its higher education and research, as well as lessons learned from this for similar initiatives elsewhere. Design/methodology/approach - The study builds on a comprehensive overview and study of policy documents and scholarly literature to identify by decade the main policies and actions and the related challenges towards a European Higher Education and Research Area. Findings - The findings make clear the key rationales, challenges, shifts and lessons to be learned from 50-year European policies for the alignment of higher education. Originality/value - Its value lies in the historical overview and analysis of current initiatives, in particular the European Universities Initiative (EUI), to provide a historical and geographical context, which might give insight for similar initiatives elsewhere.